Frequency and Variability in Errors in the Use of English Prepositions - Rosa María Jiménez Catalán (Miscelánea: A Journal of English and American Studies, 1996)
The purpose of this study is: a) to determine the frequency of preposition errors in a descriptive composition written by Spanish secondary students; b) to prove the systematicity of these errors in students from different state secondary schools; c) to carry out a tentative qualitative analysis of the variability of prepositional errors in terms of their formal classification, and in terms of the linguistic contexts in which they occur. Although percentages differ from one school to another, the results show that preposition errors are the most common of all errors. Results also show considerable difference in the frequency of error types: substitution errors are far more common than omission or addition errors. We have also obtained evidence that preposition errors seldom appear in linguistic contexts such as preceding non-finite -ing clauses and stranded-preposition constructions including wh-questions and zero-relative clauses.